The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jpln.201900283
|View full text |Cite
|
Sign up to set email alerts
|

Review Article. What are the nature and formation conditions of hydroxy‐interlayered minerals (HIMs) in soil?

Abstract: Primary minerals of the parent material undergo weathering during the formation of terrestrial soils to varying extent. As a result, secondary minerals develop, which comprise, among many others, hydroxy-interlayered minerals (HIMs). These minerals have formed by interlayering of hydroxy-metal complexes (especially of Al 3+ , also Mg 2+ , Fe 2+/3+ ) into micas, expansible 2:1 phyllosilicates and forming oligomers, or by weathering of primary chlorite. The degree of interlayer filling and the stability of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 120 publications
2
11
0
Order By: Relevance
“…When taking into account the high instability of vermiculite under acidic conditions, the low pH and low amount of HIV as a weathering product of vermiculite in the studied profile, the estimated time after decarbonization in the profile based on the Finke and Hutson's (2008) simulations becomes more realistic. In agreement with the published results (reviewed by Wilson, 1999 andGeorgiadis et al, 2020), our findings (Figure 8a,b, Tables 3 and 4) pointed out the following clay mineral assemblage: illite, chloritevermiculite -HIVsmectite is on the boundaries of mineral stability. Our interpretation partly correlates with the rate of the Luvisol-forming processes, which is based on the method of chronosequences, similarly to Alexandrovskiy (2007).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…When taking into account the high instability of vermiculite under acidic conditions, the low pH and low amount of HIV as a weathering product of vermiculite in the studied profile, the estimated time after decarbonization in the profile based on the Finke and Hutson's (2008) simulations becomes more realistic. In agreement with the published results (reviewed by Wilson, 1999 andGeorgiadis et al, 2020), our findings (Figure 8a,b, Tables 3 and 4) pointed out the following clay mineral assemblage: illite, chloritevermiculite -HIVsmectite is on the boundaries of mineral stability. Our interpretation partly correlates with the rate of the Luvisol-forming processes, which is based on the method of chronosequences, similarly to Alexandrovskiy (2007).…”
Section: Discussionsupporting
confidence: 93%
“…A noticeable peak at about 7.5 2θ (1.18 nm) after EG solvation, however, could indicate long-range ordering R3 illite-smectite (Moore & Reynolds Jr, 1997). The HIM (hydroxy-interlayered mineral) is positioned around 7.4-7.85 2θ; 1.2-1.13 nm in magnesium and potassiumsaturated samples after heating to 300 and 550 C (Figure 8a,b; Rich, 1968;Georgiadis, Dietel, Dohrmann, & Rennert, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These result from weathering of primary silicates in a geochemical milieu typical of early Podzol development, i.e. pH approximately > 4.5, which prevents acidic dissolution of 2:1 layers of phyllosilicates 47 . Despite the limited duration of the experiment, mimicked weathering of the topsoil showed that masking phases were easily removed.…”
Section: Resultsmentioning
confidence: 99%
“…Andrade et al (2019) ascribed the formation of HIMs to high rates of Al release during pedogenic weathering under acidic soil conditions, which influenced the interlayering of Al-polymers in the clay minerals. Interlayering is a common phenomenon in pedogenic 2:1 clay minerals, in which the interlayer materials include cations, hydrated cations, organic molecules, and hydroxide groups or sheets (Meunier 2007;Dietel et al 2019aDietel et al , 2019bGeorgiadis et al 2020). According to Rich (1968) and Meunier (2007), HIV is a fast-forming and unstable phase representing a moderately acidic and oxidizing condition that is often linked to frequent wet-dry cycles.…”
Section: Coupling Between Soil Acidity Pools and Hiv Formationmentioning
confidence: 99%